Attitudes and potential barriers towards hepatitis C treatment in patients with and without HIV coinfection. (March 2018) - Allyn, PR; O'Malley, SM; Ferguson, J; Tseng, CH; Chew, KW; Bhattacharya, D
This study aimed to assess attitudes and potential barriers towards treatment in patients with hepatitis C virus (HCV) infection, comparing those with and without HIV coinfection. A cross-sectional survey of 82 HCV-infected adults with and without HIV was conducted in greater Los Angeles between November 2013 and July 2015. Overall, there were 53 (64.6%) with HIV coinfection, 20 (25.0%) with self-reported cirrhosis, and 22 (26.8%) with a history of prior HCV treatment. Of all, 93.2% wanted HCV treatment, but 45.9% were unwilling/unable to spend anything out of pocket, 29.4% were waiting for new therapies, and 23.5% were recommended to defer HCV treatment. HIV/HCV-coinfected patients were more likely to want treatment within one year (90.2% versus 68.2%, p  = 0.02), more willing to join a clinical trial (74.5% versus 8.0%, p  < 0.01), more willing to take medications twice daily (86.3% versus 61.5%, p  = 0.01), and more likely to prefer hepatitis C treatment by an infectious diseases/HIV physician (36.7% versus 4.0%, p  < 0.01). Of all, 77.1% of coinfected patients were willing to change antiretroviral therapy if necessary to treat HCV, but only 48.0% of patients were willing to take a medication if it had not been studied in HIV-positive patients. Treatment preferences differ between HIV/HCV-coinfected and HCV-monoinfected patients. Despite a strong willingness among the study cohort to start HCV treatment, other factors such as cost, access to medications, and provider reluctance may be delaying treatment initiation.